Effectiveness of Fistula Ligation in the Treatment of Trans sphincteric Pararectal Fistulas - Rajabov Jasur Pardabayevich (Genius Journals, 2023)
Modern treatment of chronic paraproctitis is aimed at preserving the integrity of the anal gland in order to reduce the risk of incontinence. One of these techniques is fistula intersphincter space ligation (LIFT). The article presents data on the results of organpreserving LIFT operation and compares its effectiveness with the traditional method of treatment - fistula excision with sphincter suturing. The study group included 36 patients each with transesphincteric pararectal fistulas. The primary recovery in the first group was 77.7%. Relapse of the disease occurred in 16.7% of cases by the type of intrasphincter pararectal fistula, in 5.6% a "complete" fistula was formed. In the second group, relapse occurred in 25% of cases and exclusively as a "complete" fistula. The phenomena of incontinence were observed only in the control group
Keywords: Fistula excision; sphincter-preserving techniques; intersphincter space